2022
DOI: 10.1136/bmjopen-2021-056009
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of optimal adherence and predictors for a low level of adherence among HIV/AIDS-infected adults in South Gondar zone, Northwest Ethiopia: a multifacility cross-sectional study

Abstract: ObjectivesThis study aims to identify levels of adherence to antiretroviral therapy (ART) drugs and factors associated with them in Northwest Ethiopia. We hypothesise that in the era of COVID-19, there would be suboptimal adherence to ART drugs.DesignAn observational cross-sectional study was conducted. Factors associated with the level of adherence were selected for multiple logistic regressions at a p value of less than 0.2 in the analysis. Statistically significant associated factors were identified at a p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…12 According to Zewude et al 74.5% of individuals were married, which is different from what the current study found. 11 It was found from our study that opportunistic infections were more during COVID-19 pandemic. This may be due to reduced immune response due to poor adherence during the pandemic, as accessibility was the issue due to strict lock down measures.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…12 According to Zewude et al 74.5% of individuals were married, which is different from what the current study found. 11 It was found from our study that opportunistic infections were more during COVID-19 pandemic. This may be due to reduced immune response due to poor adherence during the pandemic, as accessibility was the issue due to strict lock down measures.…”
Section: Discussionmentioning
confidence: 53%
“…According to a study by Rodriguez et al 50.2% of participants were between the ages of 25 and 34, and the average age was 48.9±12.3 years. 7,11 Compared to a study by Campbell LS, where 68% of participants had either no education, only primary education, or some secondary education, the majority had completed education up to secondary school in the current study. 12 According to Zewude et al 74.5% of individuals were married, which is different from what the current study found.…”
Section: Discussionmentioning
confidence: 64%
“…The forty-two studies [ 1 – 3 , 5 , 6 , 8 – 10 , 18 , 19 , 27 , 29 , 34 , 43 , 44 , 52 – 78 ], two studies [ 79 , 80 ] and one study [ 35 ] were conducted using cross-sectional, retrospective cohort and case-control studies respectively. Regarding geographical region, fourteen studies were conducted in Oromia [ 2 , 3 , 9 , 18 , 27 , 44 , 52 , 57 , 59 , 64 , 69 , 76 , 77 , 79 ], eleven studies in Amhara [ 1 , 6 , 19 , 56 , 61 , 66 – 68 , 73 , 75 , 78 ], ten studies in Southern nations nationalities [ 5 , 10 , 34 , 35 , 43 , 53 , 55 , 60 , 62 , 72 ], two studies in Addis Ababa [ 8 , 44 ], two studies in Tigray [ 58 , 80 ], one study in Oromia and Southern nations nationalities [ 54 ], one study in Harari and Dire Dawa [ 63 ] and one study was conducted in each Benishangul Gumuz [ 71 ], Somali [ 74 ], Harari [ 29 ], and Sidama region [ 65 ]. The total sample size of ...…”
Section: Resultsmentioning
confidence: 99%
“…The quality of each study was evaluated using the Joanna Briggs Institute (JBI) quality appraisal criteria [ 81 ]. Forty-two studies [ 1 – 3 , 5 , 6 , 8 – 10 , 18 , 19 , 27 , 29 , 34 , 43 , 44 , 52 – 78 ], two studies [ 79 , 80 ] and one study [ 35 ] were appraised using JBI checklist for cross-sectional, cohort and case-control studies respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with previous studies conducted in Sub Saharan African countries, including Ethiopia. Pill burden, adverse effects of anti-TB medication and fear of stigma among people with TB/HIV co-infection have been documented to be more common compared to people with TB only [6,27,[32][33][34]. Furthermore, less motivation to take medication among people with TB/HIV co-infection has been reported in studies conducted in Sub-Saharan Africa [35,36].…”
Section: Discussionmentioning
confidence: 99%